Pengaruh Karaginan dari Rumput Laut Merah (Eucheuma cottonii) Asal Provinsi Aceh sebagai Edible Coating terhadap Ketahanan Buah - Reni Silvia Nasution; Husnawati Yahya; Muhammad Ridwan Harahap (Al-Kimia, 2019)
The coating substance on tomato, apple, and kiwi from carrageenan of Eucheuma cottonii that originated from Aceh was made with additional PEG (polyethylene glycol) plasticizer to increase the fruit shelf life. Carrageenan of Eucheuma cottonii was extracted using 14% alkaline solution (KOH) and precipitated using IPA (isopropyl alcohol). The coating substance was made using various combination of carrageenan (0,1%, 0,2% 0,3%) and PEG (polyethylene glycol) with concentration 0,5% (v/v). Fruit coating process was carried out by immersion until the whole fruit well submerge. The examination was carried out through functional groups identification of carrageenan from Eucheuma cottonii and the coating substance. The coating substance was observed toward fruits resistance to see changes in physical shape and hardness of fruit and used a microscope with 450 times enlargement to observe the fruit surface at 0 day, 6th day, 12th day and 18th day. As the result, carrageenan that extracted from red seaweed (Eucheuma cottonii) shown the suitable structure with the commercial carrageenan. From the observation result, coated fruits resistance which was observed at 12th day shown apple and tomato have a better hardness and physical appearance with 0,3% carrageenan than with 0,1%, 0,2%, and control, meanwhile for kiwi with 0,2% carrageenan.